Measuring the Role of the International Labor Organization (ILO) in Tackling Child Labor in Latin America - Joe Cancelo (International Journal of Science and Society, 2019)
This study aims to analyze the role of the International Labor Organization (ILO) in Dealing with Children Detained in Latin America, especially Brazil. The research method used uses qualitative methods. The results found that Brazil is a country with a high number of child laborers in the world. Responding to issues concerning child labor which are quite alarming, the Brazilian government is looking for various solutions to reduce the number of child laborers. The proposed solution is not only the formation of rules and regulations but also practical efforts such as Bolsa Familia. However, to realize this effort to obtain significant results, the government worked with several other international actors.